1996
DOI: 10.1021/jf950711u
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of l-Ornithyltaurine·HCl and the Effect on Saltiness in a Food Material

Abstract: A new convenient synthesis of a salty peptide, ornithyltaurine (Orn-Tau), was designed. Compared with a conventional synthesis, the process was shortened by two steps and the purification was made much easier in the new one. Consequently, Orn-Tau was easily obtained and subjected to a further series of experiments. The product produced a good saltiness without Na+ in the presence of HCl, and the saltiness became stronger as the amount of added HCl increased. The best quality of saltiness was obtained by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…They suggest that salt taste perceptions and preferences are unrelated to total dietary salt intake. Nakamura et al (1996) have shown that ornithyltaurine hydrochloride is as salty as salt on a molar basis, and could replace salt in some foods. They suggest a 50 per cent substitution of salt in soy sauce.…”
Section: Sensory Effectsmentioning
confidence: 99%
“…They suggest that salt taste perceptions and preferences are unrelated to total dietary salt intake. Nakamura et al (1996) have shown that ornithyltaurine hydrochloride is as salty as salt on a molar basis, and could replace salt in some foods. They suggest a 50 per cent substitution of salt in soy sauce.…”
Section: Sensory Effectsmentioning
confidence: 99%
“…designed a new method to synthesize Orn‐Tau peptides containing ornithine. In the presence of hydrochloric acid, Orn‐Tau was saltier, and the salinity increased with the increased concentration of hydrochloric acid 86 . Chen et al .…”
Section: The Methods Of Reducing Sodiummentioning
confidence: 99%
“…The results are shown in Table II. (2) Preparation of low sodium chloride-containing soy sauce. In the manner described previously,l) a variety of low sodium chloride-containing soy sauce samples were prepared by adding sodium chloride and various salty substances to pre-soy sauce.…”
Section: Preparation Of the Sample Solutionsmentioning
confidence: 99%
“…We have recommended ornithyltaurine hydrochloride as the most effective salty peptide, but have not yet reported the preparation of a low sodium chloridecontaining soy sauce by adding this peptide. Nakamura et al 2) have recently established in our laboratory a new synthetic route for ornithyltaurine. They took advantage of the fact that ornityltaurine and its intermediates were all readily soluble in water and carried out all synthetic steps in an aqueous solution to obtain an intermediate of ZOrn-(Z)-Tau-OH as the barium salt in a precipitate.…”
mentioning
confidence: 99%